Influencing factors towards customer's choice of Umrah travel agencies / Nur Aliaa Diyana Md. Hanif - Md. Hanif, Nur Aliaa Diyana (Academy of Contemporary Islamic Studies, 2018)
Nowadays, too many fraud cases that involve in Umrah package that are arrange by certain travel agency. We as Muslim Malaysian are disallowed to go to Umrah by ourselves or in other term "Do It Yourself (D.I.Y)", we cannot avoid but still need to choose which Umrah travel agency we want to pick. By that there is a problem which is how the customer need to choose to avoid from being cheating and to make them clear what they really need in the Umrah travel agency. This research aim is to study the influencing factors towards customer's choice of Umrah travel agency. It is generally studied in public Muslim Malaysia but in specifically Muslim Malaysia that are also customer of Tabung Haji. This research is based on data obtained from survey questionnaire that polled public attitudes regarding the influencing factors towards customer's choice of Umrah travel agency. The data was analysed to evaluate and determine the major factor that influence customer's choice of Umrah travel agency. The research suggested that the most influence factor is trust on travel agency. The results of the study also shown that the other factor that may influence in choosing Umrah travel agency is the factor of quality customer services. It is hope that the study can contribute to the improvement of Umrah travel agency arrangement and marketing also give a clear view to the customer that ned to choose Umrah travel agency.